Gradient-based Interpolation and Sampling for Real-time Rendering of Inhomogeneous, Single-scattering Media - Ren, Zhong; Zhou, Kun; Lin, Steve; Guo, Baining (Computer Graphics Forum, 2008)
We present a real-time rendering algorithm for inhomogeneous, single scattering media, where all-frequency shading effects such as glows, light shafts, and volumetric shadows can all be captured. The algorithm first computes source radiance at a small number of sample points in the medium, then interpolates these values at other points in the volume using a gradient-based scheme that is efficiently applied by sample splatting. The sample points are dynamically determined based on a recursive sample splitting procedure that adapts the number and locations of sample points for accurate and efficient reproduction of shading variations in the medium. The entire pipeline can be easily implemented on the GPU to achieve real-time performance for dynamic lighting and scenes. Rendering results of our method are shown to be comparable to those from ray tracing.